Differential impact of marine debris ingestion during ontogenetic dietary shift of green turtles in Uruguayan waters. (February 2018) - Vélez-Rubio, G.M.; Teryda, N.; Asaroff, P.E.; Estrades, A.; Rodriguez, D.; Tomás, J.
Abstract: Anthropogenic debris ingestion has been reported for green turtles in all their life stages worldwide. The aim of the present study is to evaluate the marine debris ingestion by green turtles stranded in Uruguayan coast between 2005 and 2013. Debris items were categorized and quantified by frequency of occurrence, relative weight, volume and number of items. A total of 96 dead stranded turtles were analyzed and 70% presented debris in their guts. The majority of debris found were plastic, being hard plastics the most abundant in weight. We found no differences in debris ingestion in stranded turtles a long the Uruguayan coast. However we detected a negative correlation between the presence of debris and turtle's size. Smaller turtles are new recruits to neritic grounds indicating that the early juvenile stage of this species is the most vulnerable to this threat in the Southwestern Atlantic. Highlights: Marine debris ingestion is one of the main threats affecting juvenile green turtle in Uruguayan coastal waters. The ingestion of debris increases in the last years of the study period. Hard plastic is the main debris category found in the digestive tract of juvenile green turtles. Green turtles recently recruit to neritic grounds presented more debris, indicating the early juvenile stage is the most affected in the South Atlantic.